2014
DOI: 10.1038/psp.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Obinutuzumab (GA101) in Chronic Lymphocytic Leukemia (CLL) and Non‐Hodgkin's Lymphoma and Exposure–Response in CLL

Abstract: Treatment regimens involving obinutuzumab (GA101) demonstrated increased efficacy to rituximab in clinical trials for non-Hodgkin's lymphoma (NHL) and chronic lymphocytic leukemia (CLL). However, the pharmacokinetic (PK) properties and the exposure–response relationships of obinutuzumab still need to be fully described. Data from four clinical trials of obinutuzumab were analyzed to describe the PK properties in patients with NHL or CLL and the pharmacodynamic (PD) properties in patients with CLL. A population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 44 publications
(68 reference statements)
11
88
2
Order By: Relevance
“…In a separate detailed PK analysis, bodyweight was shown to not have a clinically significant effect on the PK of obinutuzumab. 31 The observation that women with NHL had higher obinutuzumab exposure than men is similar to previous observations with rituximab PK in elderly DLBCL patients. 32,33 Elderly females with DLBCL who received rituximab plus CHOP therapy had slower rituximab clearance and improved PFS versus elderly males; however, these trends were not seen for younger patients.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In a separate detailed PK analysis, bodyweight was shown to not have a clinically significant effect on the PK of obinutuzumab. 31 The observation that women with NHL had higher obinutuzumab exposure than men is similar to previous observations with rituximab PK in elderly DLBCL patients. 32,33 Elderly females with DLBCL who received rituximab plus CHOP therapy had slower rituximab clearance and improved PFS versus elderly males; however, these trends were not seen for younger patients.…”
Section: Discussionsupporting
confidence: 78%
“…This observation is supported by findings from the recent PK analysis, where sex did not have a clinically significant effect on the PK of obinutuzumab. 31 Our data revealed a relationship between serum concentrations of obinutuzumab and base-line tumor burden: in patients with high base-line tumor burden who received low-dose obinutuzumab (400/400 mg), antibody PK was highly variable. In contrast, the PK of the higher obinutuzumab dose was more homogeneous and independent of base-line tumor burden.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…50,54,55 In CLL patients, a phase 1/2 study suggested a dose-response relationship and an influence of tumor burden. 56 This was further confirmed by retrospective analysis of PK data 53 and also suggested by a prospective randomized phase 2 trial. 57 Finally, the same dosing regimen as for NHL patients was applied for CLL.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 55%
“…51 In OBZ PK studies including CLL and NHL patients, the influence of BSA/weight on exposure remains controversial. 52,53 Using higher doses at the beginning of treatment in order to quickly improve exposure and saturate targets was also suggested. 50,54,55 Indeed, higher doses infused at days 1 and 8 (1600 mg) followed by infusions of 800 mg improved exposure and overall response rates (ORRs) in NHL, compared with lower doses (400 mg).…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%